GAMBARAN MAKAN, MINUM DAN CUCI TANGAN REMAJA PADA MASA PANDEMI COVID-19 - Joyeti Darni; Retno Wahyuningsih (JOURNAL HEALTH AND NUTRITIONS, 2023)
Eating and drinking habits are prone to change due to sensitivity to environmental changes in the context of a pandemic. Eating a balanced diet and drinking enough water is very important for life. One of the reasons why adolescents are categorized as vulnerable, namely changes in lifestyle and eating habits affect nutritional needs. Adequate nutritional needs need to be considered in adolescent groups to support their growth and development. This study aims to look at the description of eating, drinking and washing hands of adolescents during the Covid-19 pandemic. The research design used a cross sectional study, with adolescent respondents in the city of Mataram. Respondents were taken by random sampling and were willing to fill in informed consent. Respondents who participated amounted to 74 respondents. Data was collected using a questionnaire in December 2020. Questionnaires about drinking, reading beverage packaging labels and washing hands during a pandemic related to how many liters of water and how often teenagers wash their hands. Data were analyzed by a univariate test. The results of the study regarding the behavior of drinking water showed that as much as 50.0% of teenagers drank 8 glasses of water a day, while 17.6% of teenagers drank water only when they were thirsty. The main eating behavior is three times a day as much as 45.9% of teenagers eat the main food <3 times a day. Behavior of reading packaging labels 12.2% of teenagers always read the packaging, 4.1% of teenagers never read the packaging. Hand washing behavior during the covid pandemic 77.0% of teenagers always wash their hands.Kebiasaan makan dan minum rentan berubah karena kepekaan terhadap perubahan lingkungan dalam konteks pandemi. Makan yang seimbang dan minum air putih yang cukup, sangat penting bagi kehidupan. Salah satu alasan mengapa remaja dikategorikan rentan, yaitu perubahan gaya hidup dan kebiasaan makan berpengaruh pada kebutuhan gizi, Kebutuhan gizi yang cukup perlu diperhatikan pada kelompok remaja untuk menunjang pertumbuhan dan perkembangannya. Penelitian ini bertujuan untuk melihat gambaran makan, minum dan cuci tangan remaja selama pandemi Covid-19. Desain penelitian menggunakan cross sectional study, dengan responden remaja di Kota Mataram. Responden diambil secara random sampling dan bersedia mengisi informed consent. Responden yang berpartisipasi berjumlah 74 responden. Data dikumpulkan menggunakan kuesioner pada bulan desember 2020. Kuesioner gambaran minum, membaca label kemasan minuman dan cuci tangan selama pandemi terkait berapa banyak liter air dan seberapa sering remaja melakukan cuci tangan. Data dianalisis secara uji univariate. Hasil penelitian terkait perilaku minum air sebanyak 50.0% remaja minum air 8 gelas sehari, sedangkan 17.6% remaja minum air setiap haus saja. Perilaku makan utama 3 x sehari sebanyak 45,9% remaja makan utama <3x sehari. Perilaku membaca label kemasan 12.2% remaja selalu membaca kemasan, 4.1% remaja tidak pernah membaca kemasan. Perilaku mencuci tangan selama masa pandemi covid 77.0% remaja selalu mencuci tangan.